Azacitidine plus venetoclax in patients with high-risk myelodysplastic syndromes or chronic myelomonocytic leukaemia: phase 1 results of a single-centre, dose-escalation, dose-expansion, phase 1–2 study. Issue 10 (October 2022) - Bazinet, Alexandre; Darbaniyan, Faezeh; Jabbour, Elias; Montalban-Bravo, Guillermo; Ohanian, Maro; Chien, Kelly; Kadia, Tapan; Takahashi, Koichi; Masarova, Lucia; Short, Nicholas; Alvarado, Yesid; Yilmaz, Musa; et al.
Summary: Background: Therapies beyond hypomethylating agents such as azacitidine are needed in high-risk myelodysplastic syndromes. Venetoclax is an orally bioavailable small molecule BCL-2 inhibitor that is synergistic with hypomethylating agents. We therefore aimed to evaluate the safety, tolerability, and preliminary activity of azacitidine combined with venetoclax for treatment-naive and relapsed or refractory high-risk myelodysplastic syndromes or chronic myelomonocytic leukaemia. Methods: We did a single centre, dose-escalation, dose-expansion, phase 1–2 trial at the University of Texas MD Anderson Cancer Center (Houston, TX, USA). This Article details the phase 1 results. We enrolled patients (≥18 years) with treatment-naive or relapsed or refractory high-risk myelodysplastic syndromes or chronic myelomonocytic leukaemia and bone marrow blasts of more than 5%. No specific Eastern Cooperative Oncology Group status restriction was used. Patients were treated with intravenous or subcutaneous azacitidine (75 mg/m 2 ) for 5 days and oral venetoclax (100–400 mg) for 7–14 days. The primary outcome was safety and tolerability as well as determination of the maximum tolerated dose and recommended phase 2 dose of the azacitidine and venetoclax combination using a 3 + 3 study design. All patients who received one dose of study drug were included in the analyses. This study is registered with ClinicalTrials.gov, number NCT04160052 . The phase 2 dose-expansion part of the trial is ongoing. Findings: Between Nov 12, 2019, and Dec 17, 2021, a total of 23 patients were enrolled in the phase 1 portion of this study (17 [74%] hypomethylating agent naive and six [26%] post-hypomethylating agent failure). 18 (78%) patients were male and five (22%) were female; 21 (91%) were white and two (9%) were Asian. Median follow-up was 13·2 months (IQR 6·8–18·3). The maximum tolerated dose was not reached and the recommended phase 2 dose was established as azacitidine 75 mg/m 2 for 5 days plus venetoclax 400 mg for 14 days. The most common grade 3–4 treatment-emergent adverse events were neutropenia (nine [39%] of 23), thrombocytopenia (nine [39%]), lung infection (seven [30%]), and febrile neutropenia (four [17%]). Three deaths due to sepsis, which were not deemed treatment-related, occurred on the study drugs. The overall response rate was 87% (95% CI 66–97; 20 of 23 patients). Interpretation: Azacitidine with venetoclax is safe and shows encouraging activity in patients with high-risk myelodysplastic syndromes or chronic myelomonocytic leukaemia. Funding: MD Anderson Cancer Center.